Analisis Manajemen Program Pengendalian DBD Di Dinas Kesehatan Kota Depok Tahun 2023 - Azzahra, Makaisya; Fadli, Rina Khairunnisa (JURNAL PENDIDIKAN KESEHATAN, 2023)
In Indonesia in 2022, dengue fever increased to 131,268 people, while the number of deaths increased to 1,235 cases. Depok City is located in West Java province which has the third largest number of cases, with 2,224 cases and 14 deaths in 2022. The purpose of this study is to analyse the management at the Depok City Health Office which includes planning, organising, implementing and supervising the dengue control program. This research uses George Terry's management theory, as well as descriptive qualitative approach methodology. Primary and secondary data sources were collected through observation, interviews, and documentation. There were three informants, namely the Head of P2P Division, PJ of DHF Programme and P3M Coordinator. The data analysis used was Data Reduction, Data Display, and Verification. Triangulation of methodology and sources is part of data validation. The results of this study show that the management of the DHF control programme at the Health Office has been implemented, but it has not been effective because in its implementation it still does not have sufficient fogging equipment and the community always asks for fogging every time there is a case. Then, the Health Office strives for hospitals and health centres to provide real time results in recording, reporting, and confirming DHF cases. In addition, supervision has not been running optimally because the DHF programme PJ holds three health programmes and the information provided by the health office does not reach the target. The PJ Program should follow up on the submission of letters related to facilities and infrastructure, and the Depok City Health Office should optimise community outreach and education activities related to fogging, hospitals and puskesmas to improve the timeliness of submitting patient identity data, recording and reporting data, confirming DHF cases, and providing targeted information.